2019
DOI: 10.1186/s40104-019-0367-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression, molecular cloning, and characterization of porcine beta defensin 114

Abstract: Background β-defensins have attracted considerable research interest because of their roles in protecting hosts from various pathogens. This study was conducted to investigate the expression profiles of the porcine β-defensin 114 ( PBD114 ) in different breeds and in response to infections. Moreover, the function of PBD114 protein was partially investigated. Methods Six Tibetan pigs (TP) and six DLY (Duroc×Landrace×Yorkshire) pigs were slaught… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
2
9
1
Order By: Relevance
“…and Gram-negative bacteria (E. coli K88 and E. coli DH5α).The MIC for DEFB118 against S. aureus and E. coli K88 was 4 mg/L, which is lower than beta defenses obtained in previous study [38]. These results are also consistent with a previous report on the DEFB118, and both results indicated that the DEFB118 had a broad-spectrum of antibacterial activities [37].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…and Gram-negative bacteria (E. coli K88 and E. coli DH5α).The MIC for DEFB118 against S. aureus and E. coli K88 was 4 mg/L, which is lower than beta defenses obtained in previous study [38]. These results are also consistent with a previous report on the DEFB118, and both results indicated that the DEFB118 had a broad-spectrum of antibacterial activities [37].…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies indicated that the β-defensins has multidirectional biological properties, including antiviral, antibacterial, and anti-inflammatory effects [20,21]. For instance, β-defensin 114 was found to show antimicrobial activities against E. coli DH5α and E. coli K88 [22]. While, β-defensin 129 was reported to attenuate intestinal inflammation and epithelial atrophy in rat exposure to bacterial endotoxin [14].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, antimicrobial activity assays showed that DEFB118 has significant antimicrobial activity against both the Gram-positive bacteria ( S. aureus and B. subtilis ) and Gram-negative bacteria ( E. coli K88 and E. coli DH5α ). The MIC for DEFB118 against S. aureus and E. coli K88 was 4 mg/L, which is lower than beta defenses obtained in previous study [ 22 ]. These results are also consistent with a previous report on the DEFB118, and both results indicated that the DEFB118 had a broad spectrum of antibacterial activities [ 36 ].…”
Section: Discussioncontrasting
confidence: 63%
“…Recent studies indicated that the β -defensins have multidirectional biological properties, including antiviral, antibacterial, and anti-inflammatory effects [ 20 , 21 ]. For instance, β -defensin 114 was found to show antimicrobial activities against E. coli DH5 α and E. coli K88 [ 22 ], while β -defensin 129 was reported to attenuate intestinal inflammation and epithelial atrophy in rat exposure to bacterial endotoxin [ 14 ]. The human β -defensin 118 (DEFB118) is a novel identified HDP, which is present in the epithelial cells of different ducts and most abundant in the caput epithelium, where it is present in the lumen and located on sperm [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…pBD1 is the first beta defensin discovered in pigs, and it has lower bactericidal activity compared with pBD2, which has strong antibacterial activity against both Gram-negative and Gram-positive bacteria including multi-resistant bacteria [ 6 , 7 , 8 ]. To date, pBD2 has perhaps the strongest antimicrobial activity known among pBDs [ 6 , 9 , 10 ]. Oral administration of pBD2 reduces the inflammatory response in weaned piglets infected with E. coli [ 11 ], and pBD2 attenuates inflammation and mucosal lesions in dextran sodium sulfate-induced colitis in mice [ 12 ].…”
Section: Introductionmentioning
confidence: 99%